2021
DOI: 10.1186/s43058-021-00114-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding constraints on integrated care for people with HIV and multimorbid cardiovascular conditions: an application of the Theoretical Domains Framework

Abstract: Background People with HIV (PWH) experience increased cardiovascular disease (CVD) risk. Many PWH in the USA receive their primary medical care from infectious disease specialists in HIV clinics. HIV care teams may not be fully prepared to provide evidence-based CVD care. We sought to describe local context for HIV clinics participating in an NIH-funded implementation trial and to identify facilitators and barriers to integrated CVD preventive care for PWH. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…For patients with uncontrolled CVD-related conditions, HIV specialists reported that they first managed the conditions, including titration of CVD medications up to the provider’s level of comfort and confidence after which they would refer their patients to cardiologists mostly for medication management. In previous studies, HIV specialists were found to have low levels of comfort and confidence prescribing CVD-related medications, and the involvement of cardiologists in CVD medication management may be necessary [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with uncontrolled CVD-related conditions, HIV specialists reported that they first managed the conditions, including titration of CVD medications up to the provider’s level of comfort and confidence after which they would refer their patients to cardiologists mostly for medication management. In previous studies, HIV specialists were found to have low levels of comfort and confidence prescribing CVD-related medications, and the involvement of cardiologists in CVD medication management may be necessary [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“… 42 Managing complex treatment regimens associated with multiple chronic conditions is challenging in the case of PWH, and often care for HIV takes priority. 19 Many chronic comorbidities are also discordant with HIV (ie, not directly related in pathogenesis or management) and care for these conditions can remain suboptimal. 20 , 21 , 43 However, contemporary advances in primary care guidance may help reduce some treatment discordances.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Some comorbidities have treatment recommendations that are discordant with HIV care, and in PWH, this can create a difficult choice between managing their HIV and conditions that potentially increase their risk for CVDs. 19 , 20 , 21 Previous studies have examined multimorbidity in people with established CVDs, but there is less research examining the association between multimorbidity and incident CVD. 22 The impact of multimorbidity burden on the risk of incident HF, especially among PWH and PWoH, is largely unknown.…”
mentioning
confidence: 99%
“…The National Heart, Lung, and Blood Institute has taken note and is now funding five research teams conducting implementation studies to combat chronic comorbidities experienced by those with HIV, many of which are cardiovascular [61]. There are a variety of interventions that include nursing led care coordination for blood pressure and cholesterol management, patient activation strategies for ASCVD risk reduction, and behavioral economics informed feedback for providers through peer comparisons of statin prescription [19,61]. Another study, recognizing the contribution of mental illness to CVD in PLWH, addresses patients' trauma history to increase engagement in care [61].…”
Section: Strategies For Improvementmentioning
confidence: 99%
“…Taken together, these factors contribute to elevated CVD risk but also increase barriers to CVD prevention and therapy among PWH. Understanding and addressing these factors in a comprehensive, integrated manner is necessary to achieve progress in CVD prevention and treatment of PWH [19]. Accordingly, this review focuses on these unique areas of CVD risk among PWH, with a particular focus on major gaps and emerging practical targets to reduce CVD risk and morbidity among PWH (Fig.…”
Section: Introductionmentioning
confidence: 99%